Institutionalizing self of microcelebrity; new social control mechanism by the new form of civil power - Fatkhur Rozi, Romdhi; Ida, Rachmah; Irawanto, Budi (Technium Social Sciences Journal, 2023)
This article will investigate how a microcelebrity YouTuber named Rius Vernandes became a symbol for the birth of civil power in a digital society. His criticism vlog for Garuda Indonesia’s business class services has drawn criticism from the airline, which has led to a legal case. Through the power of social media networks and YouTube, Rius Vernandes did what came to be called self-institutionalizing, by then breaking down the limits of social control through a new force; I am a YouTuber. This article uses an exploratory approach to the development of the case to the conclusion that the case was stopped reporting by related parties. Through a theoretical study of the technique of self-representation, this paper examines how the cultural logic of the celebrification process of Rius Vernandes, led to the "victory" of civil power. The phenomenon of micro-celebrity in this paper is assumed as the construction of identity and self image in front of peer-users, to get public sympathy and attention for the freedom of criticism. The exploration is emphasized on how the strategic steps taken by Rius Viernandes by placing themselves as part of a critical digital community. The case has become one of the contemporary phenomena of the revolutionary power of criticism, breaking the border of social control by the new form of civil power through the internet in the era of digital media.